Endoscopy in 2017: a national survey of practice in the UK. Issue 1 (24th April 2018) - Shenbagaraj, Lavanya; Thomas-Gibson, Siwan; Stebbing, John; Broughton, Raphael; Dron, Michael; Johnston, Debbie; Shaw, Tim; Haboubi, Hasan Nadim; Green, John T
Abstract : Introduction: The Joint Advisory Group on Gastrointestinal Endoscopy (JAG), hosted by the Royal College of Physicians, London, oversees the quality assurance of endoscopy services across the UK. Additional questions focusing on the pressures faced by endoscopy units to meet targets were added to the 2017 annual Global Rating Scale (GRS) return. This provides a unique insight into endoscopy services across all nations of the UK involving the acute and non-acute Nation Health Service sector as well as the independent sector. Methods: All 508 services who are registered with JAG were asked to complete every field of the survey online in order to submit their completed April 2017 GRS return. Results: A number of services reported difficulty in meeting national waiting time targets with a national average of only 55% of units meeting urgent cancer wait targets. Many services were insourcing or outsourcing patients to external providers to improve waiting times. Services are striving hard to increase capacity by backfilling lists and working weekends. Data collection was done in most units to reflect productivity but not to look at demand and capacity. Some of the units did not have an agreed capacity plan. The Did Not Attend rates for patients in the bowel cancer screening programme were much lower compared with standard lists. Conclusion: This review highlights the increased pressure endoscopy services are under and the 'just about coping' situation. This is the first published overview of different aspects of UK-wide endoscopy services and the future challenges.